Belief without borders: inside the minds of the spiritual but not religious - Mercadante, Linda A. (Oxford University Press, 2014)
A dramatic rise in 'nones' - individuals without religious affiliation - has taken place in less than two decades. Many of these people are seekers who self-identify as 'spiritual but not religious (SBNR).' In this book, theologian Linda Mercadante, once an SBNR herself, sets out to find them and let them speak for themselves.